Story in Children's Lives: Contributions of the Narrative Mode to Early Childhood Development, Literacy, and Learning - Kerry-Moran, Kelli Jo; Aerila, Juli-Anna (Educating the Young Child, Advances in Theory and Research, Implications for Practice, 2019)
X, 371 p. 60 illus.